Puerperal Group A Streptococcal sepsis: a case report - J., Nithya; G., Sathyamurthy; R., Balavinoth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Group A Streptococcal (GAS) sepsis in puerperium is one of the recognised causes of maternal mortality. Though the onset is often insidious, it can progress rapidly to a life-threatening invasive infection, toxin-mediated shock, and end-organ failure, even before clinical signs become apparent. We report a case of puerperal GAS sepsis that was successfully managed. 24-years-old para 1 was readmitted to the intensive care unit requiring non-invasive ventilation on postnatal day 6 with clinical and biochemical features of sepsis. Blood culture, episiotomy wound swab, and high vaginal swab grew GAS. Broad-spectrum antibiotics initiated. She developed ascites that progressively increased and needed therapeutic paracentesis. She was discharged after four weeks of hospitalization. Early identification and prompt treatment are the keys to prevent severe morbidity and maternal mortality.